Barriers and channels formed by tight junction proteins II - Fromm, Michael; Schulzke, Jorg-Dieter; New York Academy of Sciences (Boston, Mass. : Published by Wiley-Blackwell Pub. on behalf of the New York Academy of Sciences, 2012)
Includes bibliographical references